The Existential-Phenomenological Paradigm: The Importance for Psychotherapy Integration (Existential Analysis: Journal of the Society for Existential Analysis, 2003)
Psychotherapy integration is currently an area of huge interest for those professions that deem themselves scientist-practitioners – this of course includes counselling psychology. At a theoretical level we can see a range of texts exploring and presenting models of integration (Palmer and Woolfe, 2000; Ryle, 1990). At the level of service delivery we see a range of government directives indicating that psychologists need to consider integration as the 'thread and butter approach' to mental health services with 'Level B' forms of psychotherapy predominating (NHSE, 1996). The complexity of these literatures provides many a challenge for the training of clinical and counselling psychologists and the practice of psychological therapies. This paper describes the phenomenology of several counselling psychologists as they rose to the challenges of the complex task of integration – as a trainer and as trainees.